Anthropocene futures: Linking colonialism and environmentalism in an age of crisis. (February 2020) - Erickson, Bruce
The universal discourse of the Anthropocene presents a global choice that establishes environmental collapse as the problem of the future. Yet in its desire for a green future, the threat of collapse forecloses the future as a site for creatively reimagining the social relations that led to the Anthropocene. Instead of examining structures like colonialism, environmental discourses tend to focus instead on the technological innovation of a green society that "will have been." Through this vision, the Anthropocene functions as a geophysical justification of structures of colonialism in the services of a greener future. The case of the Canadian Boreal Forest Agreement illustrates how this crisis of the future is sutured into mainstream environmentalism. Thus, both in the practices of "the environment in crisis" that are enabled by the Anthropocene and in the discourse of geological influence of the "human race, " colonial structures privilege whiteness in our environmental future. In this case, as in others, ecological protection has come to shape the political life of colonialism. Understanding this relationship between environmentalism and the settler state in the Anthropocene reminds us that the universal discourse of the Anthropocene is intertwined with the attempt to sustain whiteness into the future.